Internal market orientation: an empirical research in hotel sector - Ruizalba-Robledo, José Luis; Bermúdez-González, Guillermo José; Rodríguez-Molina, Miguel Ángel; Blanca-Mena, María José (Elsevier, 2014)
The study has three aims. First, to measure internal market orientation second, to analyze the relationships between IMO and two organizational consequences: job satisfaction and commitment; and third, to incorporate a new sub-dimension work/family balance. Empirical research has been done in a sample of Spanish hotels. Results show that IMO is a strategic determinant of both job satisfaction and employee commitment.
Keywords: Trabajadores de los servicios-Actitudes; Internal market orientation (IMO); Job satisfaction; Organizational commitment; Work/family balance